Strategi Pendidik dalam Mengantisipasi Tindakan Bullying Untuk Mewujudkan Sekolah Ramah Anak - Desty Rukmayana; Sofa Muthohar (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Bullying is often a serious problem that disrupts children's comfort and safety at school. So this research aims to explore the strategies implemented by educators at Al-Azhar 29 Semarang Islamic Kindergarten in preventing bullying and creating a child-friendly school environment. The method used in this research is qualitative, with data collection techniques through interviews with school principals and educators, observation, and documentation to understand the strategies implemented in depth. The results of the research show that educators' strategies for anticipating bullying at Al-Azhar Islamic Kindergarten 29 Semarang are carried out in the form of (1) parenting activities involving parents, (2) implementing value-based learning such as inviting children to sing anti-bullying songs, (3) providing understanding and direction regarding bullying, (4) providing advice and examples of good and bad behavior, (5) creating a child-friendly school environment. Apart from that, the success of implementing educators' strategies in anticipating bullying is influenced by internal factors, namely the support of school principals and educators in school policies related to anti-bullying. Meanwhile, the obstacles are influenced by external factors, namely parents, where there are differences in parenting styles at home and at school and there is no cooperative attitude from the child's parents